Analisis Pemerangkapan radikal bebas ekstrak etanol buah beringin (Ficus benjamina Linn.) - Marlina Karundeng; Anderson Arnold Aloanis (Jurnal Kimia Fullerene, 2018)
Fruit is a source of natural antioxidants are most plentiful. This research aims to analyze the ability of fig fruit (Ficus benjamina Linn.) to scavenge 2.2-diphenyl-1-pikrilhidrazil. Ripe fig fruit macerated with ethanol for 3 × 24 hours and evaporated. Ethanol extract of fig fruit then tested for free radical scavenging activities and changes colour is measured by Spectrophotometer UV-Vis. Ethanol extracts of Ficus Benjamina. Linn. shows IC50 of 40.36 μg/mL.